Mesoporous Organosilica Hollow Microspheres with Hierarchical Structures on the Shell - Zhang, X.; Liu, T.; Sun, W.; Liu, Jian (American Scientific Publishers, 2013)
Hierarchical mesoporous organosilicas with hollow structures have been readily synthesized from one template approach by using Pluronic P123 as a surfactant and 1,2-bis(trimethoxysilyl)ethane as precursor in mild HAc-NaAc (pH = 4.4) buffer solution. The obtained hierarchical mesoporous organosilica hollow spheres with raspberry-like morphology have at least three level hierarchical structures: (1) hollow micro sphere (particle size of 10 to 35 μm), (2) solid nanospheres (350~600 nm), the coexistence of mesopore (pore diameter, 12 nm) and micropore (pore diameter, 0.8 nm) on the shell. It was found that the hollow spheres with smooth surface and raspberry-like morphology could be controllably synthesized by varying the stirring time. Alcohols with different chains were also investigated, the hydrophilic alcohol with more –OH such as glycerol has been found play an important role in the synthesis of such hierarchically hollow sphere. These organosilica hollow spheres with hierarchical porosity are promising candidates for applications in nanoreactors, selective sorption, and controlled release.